ASSESSMENT OF VARIABILITY IN GRAIN YIELD, SEED MORPHOMETRIC AND VIGOUR TRAITS OF EARLY MATURING HYBRID MAIZE - Ogunniyan, Dotun; Makinde, Solomon; Adetumbi, Johnson; Olasoji, Julius (Journal of Agricultural Sciences (Belgrade), 2021)
Breeding for yield and quality requires an assessment of the seed metrics and vigour traits. This study, therefore, assessed the variability and inter-dependence of grain yield (GY), seed morphometric and vigour in early maturing hybrid maize. Seeds of 75 hybrid maize were evaluated for morphometric and quality in four replicates. A field trial laid out in randomized complete block design with three replicates was also conducted on the hybrids in Ibadan, Nigeria. Data were taken on the grain yield, seed dimension and quality parameters and subjected to analysis of variance. Least Significant Difference was used to separate groups of means. Relationships among the GY, seed morphometric and vigour traits were determined using correlation coefficients while principal component (PC) analysis was performed for variability among the hybrids. Significant differences (P<0.001) existed for the GY, seed dimension and vigour traits. Four of the nine highest yielding hybrids had ECT higher than 30.0 µsg-1 cm-1. The GY correlated with SAG (-0.28*), SDT (0.40**), SWD (0.36**), SLG (0.35**), SAR (0.30**) and SVI (0.30**) while SAG significantly correlated with SDT, SLG, STH and SAR. The seed vigour correlated with one another. The PC I explained GY, SDT, SWD, SLG, SAR and SVI indicating the importance of the traits in grain yield improvement. Seed angle, length and diameter were versatile in maize varietal selection. Identified high yielding with seed morphometric and vigor qualities can be explored by seed companies as innovation in the seed production business.